How sex‐ and age‐disaggregated data and gender and generational analyses can improve humanitarian response. (11th June 2013) - Mazurana, Dyan; Benelli, Prisca; Walker, Peter
Abstract : Humanitarian aid remains largely driven by anecdote rather than by evidence. The contemporary humanitarian system has significant weaknesses with regard to data collection, analysis, and action at all stages of response to crises involving armed conflict or natural disaster. This paper argues that humanitarian actors can best determine and respond to vulnerabilities and needs if they use sex‐ and age‐disaggregated data (SADD) and gender and generational analyses to help shape their assessments of crises‐affected populations. Through case studies, the paper shows how gaps in information on sex and age limit the effectiveness of humanitarian response in all phases of a crisis. The case studies serve to show how proper collection, use, and analysis of SADD enable operational agencies to deliver assistance more effectively and efficiently. The evidence suggests that the employment of SADD and gender and generational analyses assists in saving lives and livelihoods in a crisis.